High Temperature Instabilities in Sr0.75Ba0.25Nb2O6 Ferroelectric Relaxor - Shabbir, G. (The Nucleus, 2018)
Â [001]-oriented tungsten bronze type Sr0.75Ba0.25Nb2O6 uniaxial relaxor ferroelectric single crystals have been examined by the temperature dependent complex capacitance study. The capacitance dispersion maximum temperature was observed at T 58 oC with strong frequency dependence above and below this temperature. At temperatures T>Tmax three additional instabilities were exhibited by the complex capacitance in the unpoled crystal during heating cycle whereas these instabilities could not be seen in the subsequent cooling cycle. Similarly these instabilities disappeared upon poling the crystal at room temperature. These additional high temperature instabilities of the metastable character were associated to different kinds of random inhomogeneous structures trapped in strong random field matrix of SBN-x uniaxial relaxor.